Chapter Signorie e relazioni interstatali. Opportunità e rischi del potere locale lungo la frontiera alpina dello stato di Milano (secolo XV) - Della Misericordia, Massimo (Reti Medievali E-Book, 2021)
This essay analyzes the ways in which rural lordship was legitimized, maintained and sometimes contested in the late Middle Ages. The focus is not on the local societies and the political competition within the regional state, but rather on the position of seigneurial power in the interstices of international relations. Specifically, the dynamics of the frontier allowed the lords to enforce their power, but produced situations that put their authority in risk, providing opportunities for their subjects to contrast it. Political brokerage is the key to exploring the competition and the relationship between a variety of local actors and the state authorities. The source I selected is the Carteggio sforzesco, consisting of the written correspondence between these protagonists. From this viewpoint and thanks to records rich in narrative and descriptive contents, I will try to reconstruct economic tensions, military instability, the need for diplomatic agreements and for individual protection, that define the relationship between the Duchy of Milan, Valais, Switzerland and Grisons. Finally I will go into depth in the case-study of Val Formazza, where the domination of the lords family was in decline during the 15th Century, while local protagonists of this diversified local world - highlanders of lower social conditions settled in a peripheral valley forming an ethno-cultural minority of German speakers - were capable.